Acute mastoiditis: 20 years of experience with a uniform management protocol. (October 2019) - Mansour, Tamer; Yehudai, Noam; Tobia, Amjad; Shihada, Rabia; Brodsky, Alex; Khnifies, Riad; Barzilai, Roni; Srugo, Isaac; Luntz, Michal
Abstract: Objectives: To characterize the clinical presentation of pediatric patients who, upon AM diagnosis, also had imaging-diagnosed ICCs (ID-ICCs); to define the group of AM patients at risk of developing ID-ICCs; and to update knowledge about organisms causing AM. Study design: Analysis of all AM patients admitted between 1997 and 2018 and treated according to an obligatory protocol including both brain imaging and sampling for bacterial culture upon clinical diagnosis of AM. Results: Of 166 admitted patients (0.5–19 years old) 22 (13%) already had ID-ICCs. In patients who, on admission, had already received antibiotics for acute otitis media (AOM) and also had CRP (C-reactive protein) levels above 93.5 mg/L, the risk of ID-CC was increased by 22.5-fold ( P < 0.0001). Bacterial culture results were available for all patients and were positive in 115 (69%). Organisms most commonly found in patients without prior antibiotic treatment were group A Streptococcus pyogenes (53%), Streptococcus pneumoniae (23%), and Haemophylus influenzae (11%), while with prior antibiotic treatment they were Fusobacterium necrophorum (21%), Streptococcus pyogenes (18%) and Pseudomonas aeruginosa (18%). Conclusions: Since the risk of ID-ICC in patients with the abovementioned CRP and prior antibiotic treatment was significantly higher than in the others, these high-risk patients should undergo diagnostic imaging on admission. Antibiotic treatment prior to AM development may promote growth of non-AOM pathogen.